Up! : how families around the world carry their little ones - Hughes, Susan, 1960- (Owlkids Books, 2017)
"Around the world, little ones are carried in many different ways: in slings, on shoulders, in backpacks, on hips, in baskets, and in loving arms. Up! depicts ten places around the world, from Afghanistan to northern Canada, Peru to West Africa. In each place, a mom, dad, grandparent, aunt, uncle, cousin, or sibling lovingly carries a baby. With various family configurations and settings ranging from a busy outdoor market to a high-rise apartment kitchen, the book wholeheartedly celebrates diversity. Gorgeous cut-paper collage art adds warmth and brightness, and brings the lyrical text to life. Repetition of the phrase "Upsy-daisy" on each spread lends familiarity, and reminds readers that love for a little one is a universal feeling."--